Aspects Regarding the Relationship Between Different Tax Income and Economic Growth, Analysts Opinions - Florina POPA (Communications of International Proceedings, 2023)
A number of analysts have followed, in their works, the effects of different categories of taxes (taxes on labour, capital, consumption and others) on economic growth, trying to establish to what extent they bring their contribution to growth or can have an unfavorable effect. The purpose of the paper is to identify the relationship between different types of taxes and economic growth through the prism of different specialists¢ opinions in the field, with consideration of effects brought to the economy. The motive behind the study is given by the importance of studying the impact on growth, of different types of tax revenues and its implications in the economy.
Keywords: : economic growth; tax income; taxation; impact; policy